Membangun pemahaman: eksplorasi teori pembelajaran Jerome Bruner: 1. Akses Pendidikan 2. Kualitas Pendidikan 3. Dampak Sosial dan Ekonomi 4. Solusi untuk Mengatasi Ketimpangan 5. Peran Masyarakat dan Sektor Swasta - Fuad, Fuad Ali Maskur (Maliki Interdisciplinary Journal, 2025)
This article aims to comprehensively explore the learning theory developed by Jerome Bruner, a prominent figure in cognitive psychology and education. The primary focus is on the core principles of Bruner's theory, such as discovery learning, the spiral curriculum, and the importance of structure in instructional delivery. Using a qualitative, literature-based approach, this study analyzes the relevance and application of Bruner's theory in modern educational contexts, particularly in enhancing students’ conceptual understanding through active and meaningful learning. The findings indicate that Bruner's theory emphasizes the active role of learners in the learning process, the gradual presentation of material aligned with cognitive development stages, and the role of teachers as facilitators. This theory also proves to be adaptable to various 21st-century learning models that emphasize independence, creativity, and problem-solving. Therefore, a deep understanding of Bruner’s learning theory can serve as a foundation for designing effective and student-centered learning strategies.